Decoding the impact of the placebo response in clinical trials for chronic cough - Mengru Zhang; Bangyu Zhang; Alyn H. Morice (ERJ Open Research)
Chronic cough is a prevalent and challenging condition, with limited treatment options available. The interpretation of clinical trial results for antitussive drugs is complicated by the presence of the placebo response, which can confound outcomes and impede regulatory approval. This review aims to explore the impact of the placebo response on clinical trials for cough medications and elucidate the underlying mechanisms involved. The multifaceted nature of antitussive effects, including pharmacological, psychological/neurobiological and nonspecific effects, is discussed. Additionally, potential solutions to address the placebo response in future cough medication development, such as strategic study design, appropriate choice of end-points and meticulous patient selection, are proposed. More progress to harness this issue is urgently needed.